Innovative biological approaches for monitoring and improving water quality - Aracic, Sanja; Manna, Sam; Petrovski, Steve; Wiltshire, Jennifer L.; Mann, Gülay; Franks, Ashley E. (Frontiers in Microbiology, 2015)
Water quality is largely influenced by the abundance and diversity of indigenous microbes present within an aquatic environment. Physical, chemical and biological contaminants from anthropogenic activities can accumulate in aquatic systems causing detrimental ecological consequences. Approaches exploiting microbial processes are now being utilized for the detection, and removal or reduction of contaminants. Contaminants can be identified and quantified in situ using microbial whole-cell biosensors, negating the need for water samples to be tested off-site. Similarly, the innate biodegradative processes can be enhanced through manipulation of the composition and/or function of the indigenous microbial communities present within the contaminated environments. Biological contaminants, such as detrimental/pathogenic bacteria, can be specifically targeted and reduced in number using bacteriophages. This mini-review discusses the potential application of whole-cell microbial biosensors for the detection of contaminants, the exploitation of microbial biodegradative processes for environmental restoration and the manipulation of microbial communities using phages.